Introduction to Nonprofit Organization Accounting. - Gabhart, David R. L.; Burns, Thomas J. (The Accounting Review, 1980)
The article reviews the book "Introduction to Nonprofit Organization Accounting," 3rd edition, by Emerson O. Henke.